Aplikasi Realitas Tertambah untuk 12 Gerakan Pengaturan Lalu Lintas: Augmented Reality Application For 12 Traffic Management Movements - I Nyoman Suwira Deva; Nancy Jeane Tuturoong; Sumenge Tangkawarouw Godion Kaunang (Jurnal Teknik Informatika, 2023)
In order to guarantee the safety, security, order, and smoothness of traffic, it is necessary to carry out traffic management which includes the activities of planning, regulating, supervising, and controlling traffic. However, learning about traffic science, including the science of traffic control movements, is still very minimal among the public. Meanwhile, knowledge of traffic control movements is important for the public to understand in order to create a safe and orderly atmosphere when driving on the road, and to reduce the potential for traffic accidents. So a research was made that could develop an application for recognizing 12 traffic control movements by applying augmented reality technology to the public in an easy-to-understand way. The application developed uses augmented reality technology with the image target method. Application development is carried out using the Multimedia Life Cycle (MDLC) development method. This research succeeded in producing an application that is able to introduce 12 traffic control movements by applying augmented reality technology to the public in an easy-to-understand way.